Quantification of the association between malaria in pregnancy and stillbirth: a systematic review and meta-analysis - Moore, K; Simpson, J; Scoullar, M; McGready, R; Fowkes, F (Elsevier, 2017)
Background: 2·6 million stillbirths occur annually worldwide. The association between malaria in pregnancy and stillbirth has yet to be comprehensively quantified. We aimed to quantify the association between malaria in pregnancy and stillbirth, and to assess the influence of malaria endemicity on the association. Methods: We did a systematic review of the association between confirmed malaria in pregnancy and stillbirth. We included population-based cross-sectional, cohort, or case-control studies (in which cases were stillbirths or perinatal deaths), and randomised controlled trials of malaria in pregnancy interventions, identified before Feb 28, 2017. We excluded studies in which malaria in pregnancy was not confirmed by PCR, light microscopy, rapid diagnostic test, or histology. The primary outcome was stillbirth. We pooled estimates of the association between malaria in pregnancy and stillbirth using meta-analysis. We used meta-regression to assess the influence of endemicity. The study protocol is registered with PROSPERO, protocol number CRD42016038742. Findings: We included 59 studies of 995 records identified, consisting of 141 415 women and 3387 stillbirths. Plasmodium falciparum malaria detected at delivery in peripheral samples increased the odds of stillbirth (odds ratio [OR] 1·81 [95% CI 1·42–2·30]; I2=26·1%; 34 estimates), as did P falciparum detected in placental samples (OR 1·95 [1·48–2·57]; I2=33·6%; 31 estimates). P falciparum malaria detected and treated during pregnancy was also associated with stillbirth, but to a lesser extent (OR 1·47 [95% CI 1·13–1·92]; 19 estimates). Plasmodium vivax malaria increased the odds of stillbirth when detected at delivery (2·81 [0·77–10·22]; three estimates), but not when detected and treated during pregnancy (1·09 [0·76–1·57]; four estimates). The association between P falciparum malaria in pregnancy and stillbirth was two times greater in areas of low-to-intermediate endemicity than in areas of high endemicity (ratio of ORs 1·96 [95% CI 1·34–2·89]). Assuming all women with malaria are still parasitaemic at delivery, an estimated 20% of the 1 059 700 stillbirths in malaria-endemic sub-Saharan Africa are attributed to P falciparum malaria in pregnancy; the population attributable fraction decreases to 12%, assuming all women with malaria are treated during pregnancy. Interpretation: P falciparum and P vivax malaria in pregnancy both increase stillbirth risk. The risk of malaria-associated stillbirth is likely to increase as endemicity declines. There is a pressing need for context-appropriate, evidence-based interventions for malaria in pregnancy in low-endemicity settings.